Improved mechanical properties of Al2O3-25 vol% SiCw composites prepared by oscillatory pressure sintering. Issue 17 (1st December 2017) - Zhu, Tianbin; Xie, Zhipeng; Han, Yao; Li, Shuang; An, Di; Luo, Xudong
Abstract: 25 vol% SiC whiskers reinforced Al2 O3 composites (Al2 O3 -25 vol% SiCw) were prepared in the present work by using a novel oscillatory pressure sintering (OPS) technique. For comparison, such composites were also prepared by the conventional hot pressing (HP) process. It was found that the use of the external oscillatory pressure led to a higher densification, a more homogenous microstructure and a smaller grain size of Al2 O3 matrix compared to the HP-fabricated specimen, thus improving room temperature flexural strength (741 ± 36 MPa), fracture toughness (8.18 ± 0.43 MPa m 1/2 ) and hardness (21.32 ± 0.40 GPa) of the OPS-fabricated specimen. Hence, we believe that the novel OPS process provides a promising approach to fabricate high-performance ceramic matrix composites.